Molecular Rydberg Transitions in Carboxylic Acids by RINDO/S-CI Method - Sinha, R.P.; Singh, A.N. (Asian Journal of Chemistry, 2010)
Rydberg transitions in some carboxylic acids like acetic acid, propanoic acid and butanoic acid have been calculated using semi-empirical SCF-LCAO-MO-RINDO/S-CI method. The computed transition energies, oscillator strengths and percentage Rydberg character for singlet singlet (S → S) and singlet-triplet (S → T) transitions alogwith S → T splittings are in good agreement with the experimental values.